Impact of water residence time and stratification on water quality improvement of an artificial brackish waterway - Bo-Kyung Kim; Dong Hyeon Kim; Jin Hwan Hwang (Journal of Hydrology: Regional Studies)
Study region: The Ara Waterway, an artificial inland brackish waterway in South Korea. Study focus: This study investigates how water residence time and stratification affect water quality in an artificial brackish water system, which has different characteristics from natural environments and is under-researched, using numerical simulations. Various hydrodynamic conditions, including freshwater discharge and travel distances, were analyzed to understand their impact on residence times and stratification, offering insights for optimizing water quality management. New hydrological insights for the region: This study demonstrates that stratification significantly impacts water quality more than residence time in artificial brackish waterways. In contrast to lakes or reservoirs, increasing freshwater discharge in artificial brackish waterways can enhance stratification, reducing vertical mixing and degrading water quality, especially in the bottom layers. In the F0 scenario, excluding freshwater inflow increased summer maximum dissolved oxygen by 1.37 times compared to the validation case. This suggests that breaking stratification, such as through underwater aeration systems, may be more effective than focusing on residence time. In the L15 scenario, with the longest travel distance, upstream total nitrogen and total phosphorus increased by 18.37 % and 26.12 %, while downstream levels decreased by 3.35 % and 10.52 %. Additionally, poorer quality freshwater can degrade overall water quality, even with shorter residence times. These findings emphasize the need for careful management of inflowing water to maintain water quality in artificial brackish waterways.